Online library vs physical library visit : perceptions of learners with autism spectrum disorder (ASD) / Nurshamshida Md Shamsudin and Melor Mohd Yunos - Md Shamsudin, Nurshamshida; Mohd Yunos, Melor (Universiti Teknologi MARA, 2021)
This study aims to explore perceptions of a student diagnosed with Autism Spectrum Disorder (ASD) in higher education institutions specifically in dealing with their ability to use university libraries throughout their study term. Since the promotion and dissemination of information about autism awareness have been aggressively promoted throughout society, the number of students identified with autism in higher education has been increasing. Some of the students were only aware that they had been diagnosed with Autism after experiencing difficulty adjusting to campus life. Their visits to the library are part of their acclimatization to a university learning environment. However, due to the outbreak of covid 19, the students generally ought to do their library research online rather than visiting the campus library. A qualitative approach was used in this study, which included a case study of five students from diverse faculties in a Malaysian college who were selected for the study. The result from this paper is to provide some insights into how learners with autism perceive online libraries and physical libraries, as well as the differences between the two. It is found that learners with ASD feel happier using an online library rather than a visit to a physical library and librarian competency does give an impact on their social interactions. To conclude, this study reduces the gap between research on autism learners and library services in higher education settings so that university libraries will be well prepared when they receive students with disabilities concerns.